Perception and Cognition: Interactions in the Ageing Brain - Harriet A. Allen (Frontiers Research Topics, 2016)
Healthy ageing can lead to declines in both perceptual and cognitive functions. Impaired perception, such as that resulting from hearing loss or reduced visual or tactile resolution, increases demands on 'higher-level' cognitive functions to cope or compensate. It is possible, for example, to use focused attention to overcome perceptual limitations. Unfortunately, cognitive functions also decline in old age. This can mean that perceptual impairments are exacerbated by cognitive decline, and vice versa, but also means that interventions aimed at one type of decline can lead to improvements in the other. Just as improved cognition can ameliorate perceptual deficits, improving the stimulus can help offset cognitive deficits. For example, making directions and routes easy to follow can help compensate for declines in navigation abilities. In this Topic, we bring together papers from both auditory and visual researchers that address the interaction between perception and cognition in the ageing brain. Many of the studies demonstrate that a broadening of representations or increased reliance on gist underlie perceptual and cognitive age-related declines. There is also clear evidence that impaired perception is associated with poor cognition although, encouragingly, it can also be seen that good perception is associated with better cognition. Compensatory cognitive strategies were less successful in improving perception than might be expected. We also present papers which highlight important methodological considerations that are required when studying the older brain.